2012
DOI: 10.1371/journal.pone.0034896
|View full text |Cite
|
Sign up to set email alerts
|

First Report of 13 Species of Culicoides (Diptera: Ceratopogonidae) in Mainland Portugal and Azores by Morphological and Molecular Characterization

Abstract: The genus Culicoides (Diptera: Ceratopogonidae) contains important vectors of animal and human diseases, including bluetongue, African horse sickness and filariosis. A major outbreak of bluetongue occurred in mainland Portugal in 2004, forty eight years after the last recorded case. A national Entomological Surveillance Plan was initiated in mainland Portugal, Azores and the Madeira archipelagos in 2005 in order to better understand the disease and facilitate policy decisions. During the survey, the most preva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 14 publications
1
15
0
1
Order By: Relevance
“…The capture of Culicoides biting midges from cattle, sheep, goats and horses farms was essential to characterize the distribution of Culicoides species in the country [22,23]. …”
Section: Introductionmentioning
confidence: 99%
“…The capture of Culicoides biting midges from cattle, sheep, goats and horses farms was essential to characterize the distribution of Culicoides species in the country [22,23]. …”
Section: Introductionmentioning
confidence: 99%
“…Since their introduction, several modifications to these traps have been made to improve their effectiveness, being the modern models (CDC miniature trap models 512 and 1212), the most common tools for monitoring Culicoides species. These traps have routinely been used in surveillance programs in the USA (Smith and Mullens, 2003), but also in many European countries, including France (Venail et al, 2012), Spain (Pérez et al, 2012;González et al, 2013) or Portugal (Ramilo et al, 2012). Black lights (UV) are superior to white light in terms of specimens and species collected (Venter et al, 2009), depending on the type of trap (design, size and intensity of light source, etc.…”
Section: Introductionmentioning
confidence: 99%
“…semimaculatus has previously been reported to be geographically limited to southern Europe and detected in proximity to cattle, goats and sheep [14]. So it's important to capture this species and to analyze its potential role to transmit disease.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, [17] have demonstrated that Blacklight was more attractive to vector insects than white light and increases monitoring sensitivity in areas where vector abundances are low; (2) the biotic and abiotic factors linked to the availability of suitable breeding habitats which did not occur locally and equally for all species. Indeed, in Sardinia, C. imicola and C. newsteadi occur more frequently in coastal areas at lowers altitudes, whereas C. obsoletus and Culicoides pulicaris are restricted to more mountainous central areas [14]. Previous studies have suggested that the high abundance of C. imicola is most likely linked to its preference for breeding in areas where soil is moist and nutrient-rich and with full exposure to sunlight, characteristics which are more commonly found in the centre [18].…”
Section: Discussionmentioning
confidence: 99%